(3GdeHGbd GdSHYI aj GdcjejGAs - (3eMeO Hf Cejd Hf YHO Gddg Hf Cejd GdJejej , CHh YHO Gddg , (B170 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYdejf gPg GdeHGbd GdSHYI dGHf Cejd JCed efgG WdYkG hHSQkG hHdMkG hQWHkG s
(3BNQgG (B:s
(3Ke JLjH GdQeOI hJedCgG hJOdcgG OckC LjOkG hJLjH GdTNhU GdPjf NWge WjH hJQUge JeJ GdQSGdI s
(3hgh (B7 (3CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B429 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B178 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYjGJ (B177) s
Keywords: (3GdcjejGA h GdWHjYjGJs